Perlindungan Hak Cipta terhadap Pencipta Komik Dalam Platform Digital Tapas Media - Gantina, Mochamad Ilham; Anggraeni, Happy Yulia (Wajah Hukum, 2023)
In this age of disruption, the advancement of information technology brings with it new innovations, opportunities, and challenges. One of the difficulties is the increasingly easy distribution of illegal digital products. Digital comics are one example of a copyright product that is illegally distributed. Unfortunately, the increasing popularity of digital comics is being accompanied by an increase in piracy in Indonesia. This has had a huge impact on digital comic creators, who should have had full rights to their ideas but had them taken away by irresponsible parties. The goal of this research is to learn about the legal protections afforded to digital comic creators, as well as to learn about law enforcement actions taken against perpetrators who illegally distribute digital comics on online sites. This study employs normative legal research methods to provide an overview of the major issues. According to the study's findings, copyright protection for digital comic creators is currently regulated in Copyright Law No. 28 of 2014, so that law enforcement against perpetrators of digital comics distribution on illegal sites can be pursued through mediation, civil lawsuits, criminal complaints, and the closure of content and/or access to sites that violate Copyright.